زمانۂ قبل از اسلام سے تیسری صدی ہجری تک کے عرب مغنّی اور مغنّیات کا احوال : ’ کتاب الاغانی‘ و ’طاؤس و ربابٗ کا مطالعہ (Al-Qamar, 2023)
Author of "Kitāb-Al-Aghānī" (Book of Songs), Abu-Al-Faraj Al-Isfahānī was a famous Arab author and poet. He wrote other important books also but "Kitāb-Al-Aghānī" proved a mile stone in his life works. It consisted upon the long tale of pre-Islamic period till 3rd century hijra's musicians, composers, singers and poets. This book presents the true picture of that time's Arab Society and Culture. Prof. Noor-ul-Hassan Khan,s "Tāwos-o-Rubāb" is a single example of such type of books in Urdu literature. In this book most of the references are drawn from " Kitāb-Al-Aghānī ". We can find in Urdu literature a true picture of pre-Islamic period to 3rd century hijra's cultural and moral values through this book. This article is an attempt to show the interaction between the books mentioned above.
Keywords: Kitāb-Al-Aghānī; Ayyam-ul-Arab; Arab culture; Arab musicians; Encyclopedia of Islam